The (Positive) Effect of Macroeconomic Crises on the Schooling and Employment Decisions of Children in a Middle-Income Country - Schady, Norbert R. (World Bank, Washington, DC, 2013)
The impact of macroeconomic crises on parents' investments in the human capital of their children is a widely contested issue. The author analyzes the effects of the profound macroeconomic crisis in Peru in 1988-92 on the schooling and employment decisions made by urban school-age children. He arrives at two basic findings: First, the crisis had no effect on the attendance rates of school-age children. But the share of children who were both employed and in school fell significantly during the crisis. Second, mean educational attainment was significantly higher for children who were exposed to the crisis than for those who were not. THe author argues that these findings may be related: children who are not employed have more time available and may therefore put more effort into school. He concludes with a discussion of the implications of his findings for the design of appropriate social protection policies.